2011
DOI: 10.1111/j.1365-2036.2011.04653.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome of anorectal biofeedback therapy in patients with constipation

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 30 publications
(38 reference statements)
1
41
0
3
Order By: Relevance
“…This finding is not unexpected because hard stool is a common feature of DD [1] and because BFT is known to improve dyssynergia and allow more efficient stool evacuation. Shim et al studied 102 patients with CC and reported similar findings [47].…”
Section: Discussionsupporting
confidence: 60%
“…This finding is not unexpected because hard stool is a common feature of DD [1] and because BFT is known to improve dyssynergia and allow more efficient stool evacuation. Shim et al studied 102 patients with CC and reported similar findings [47].…”
Section: Discussionsupporting
confidence: 60%
“…Harder stool consistency, shorter duration of laxative use, higher resting anal sphincter pressure, and more prolonged balloon expulsion time have been reported as predictors of a desirable outcome. 185,186 Neither patient age nor gender significantly affect the outcome. 186 The patient's willingness to participate or compliance is basically required for a behavioral therapy and seems to be one of the most important factors.…”
mentioning
confidence: 99%
“…185,186 Neither patient age nor gender significantly affect the outcome. 186 The patient's willingness to participate or compliance is basically required for a behavioral therapy and seems to be one of the most important factors.…”
mentioning
confidence: 99%
“…A recent study indicated that only 44-48% of patients who were recommended BFT actually underwent BFT10 because of the lack of insurance coverage, distance to local treatment facilities, and acute medical issues taking precedence. Moreover, BFT is time-consuming, and repeated training is required; hence, a willingness to participate is important for successful BFT 35. Physicians and therapists need to continuously motivate patients through education and counseling.…”
Section: Limitations Of Biofeedback Therapymentioning
confidence: 99%